2015
DOI: 10.1021/acsami.5b04226
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon-Encapsulated PLGA-PEG Emulsions as Enhancement Agents for Highly Efficient Reoxygenation to Cell and Organism

Abstract: Perfluorocarbon (PFC), a kind of oxygen carrier, is encapsulated in PLGA-PEG to prepare a PLGA-PEG/PFC emulsion for highly efficient reoxygenation to cell and organism. HCT 116 cells are used as a model cell, whose viability has a significant enhancement after reoxygenation with PLGA-PEG/PFC emulsion because of the sufficient and timely oxygen supply. Meanwhile, hypoxia-reoxygenation injury will happen along with cell hypoxia-reoxygenation treatment, which is reflected by increasing reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…166 Researches have also shown that perfluorocarbons can prolong cell survival under hypoxic environment owing to the controlled release of oxygen. 171-173 Therefore, perfluorocarbons are potentially valuable oxygen modulators and should be of great potential to replenish oxygen consumption and promote ROS generation in PDT studies. 174, 175 …”
Section: Oxygen Self-supplementmentioning
confidence: 99%
See 1 more Smart Citation
“…166 Researches have also shown that perfluorocarbons can prolong cell survival under hypoxic environment owing to the controlled release of oxygen. 171-173 Therefore, perfluorocarbons are potentially valuable oxygen modulators and should be of great potential to replenish oxygen consumption and promote ROS generation in PDT studies. 174, 175 …”
Section: Oxygen Self-supplementmentioning
confidence: 99%
“…170, 173, 176, 177 Specifically, oxygen-favoring PDT would deplete oxygenation level through photochemical consumption and occlusion of blood vessels. 146 Therefore, perfluorocarbon-integrated PDT with a continuous supply of molecular oxygen could be an innovative strategy to diminish the oxygen dependence.…”
Section: Oxygen Self-supplementmentioning
confidence: 99%
“…[33][34][35][36] Furthermore, it has been demonstrated that liquid perfluorocarbon compounds (PFC) act as a good oxygen carrier 37 and are widely used in ultrasound imaging, and PLGA NPs entrapped with PFC droplets have been reported in several studies. [38][39][40] So far, there is no report about the establishment and application of PLGA NPs delivering ICG and oxygen simultaneously.…”
mentioning
confidence: 99%
“…Fraker et al found particle size to be a critical factor affecting oxygen mass transfer from PFC containing colloidal systems and optimized the manufacture of nano-scale emulsion [7]. PFC were also encapsulated into biodegradable nanoparticles composed of PEGylated PLGA, as enhancement agents for efficient re-oxygenation to cells and organisms [8].…”
Section: Ocimum Scientific Publishersmentioning
confidence: 99%